Recommendations for Early Phases of Engaging Communities in Climate Change Adaptation - Richard R. Plate; Martha C. Monroe; Claire Friedrichsen; Allison W. Bowers; Willandia A. Chaves (Journal of Human Sciences and Extension, 2020)
Communities across the globe have begun planning for and adapting to climate change. Cooperative Extension Service professionals are in a unique position to use the resources available to them to facilitate climate change adaptation in their communities. Adaptation planning is a local activity that must be context specific. However, general recommendations can be made to help facilitate the planning process. In this study, we conducted a systematic review of research about climate change adaptation in communities to explore ideas that contribute to successful adaptation-planning communication. We identified and reviewed 50 peer-reviewed articles that described various outreach efforts to engage communities in planning for adaptation across a range of contexts and settings. Five themes emerged addressing how to facilitate early stages of the climate change adaptation process: establishing positive initial engagement, incorporating participatory methods, using tools to facilitate understanding, addressing trust and uncertainty, and maximizing limited time. Based on the review and emergent themes, we offer practical recommendations for educators and Cooperative Extension Service professionals as they engage communities in climate change adaptation.